Pencatatan Perkawinan Beda Agama : (Analisis Penetapan Nomor: 508/Pdt.P/2022/PN.JKT.SEL) - Dewi Andriani; Sahruddin Sahruddin; M. Yazid Fathoni (Fakultas Hukum Universitas Mataram, 2023)
This study's purpose is to determine the regulation of interfaith marriages, the judges' legal considerations determine, the position of children in interfaith marriages. This research is a normative legal research method. The results of this study: 1) The regulation for interfaith marriages, namely the Civil Code, HOCI, Staatsblad No.158/1898, Act Number 1 of 1974 concerning Marriage, Presidential Instruction No. 9 of 1991 concerning Islam Law Compilation, Supreme Court Decision Jurisprudence No.1400/K/Pdt/1986, Constitutional Court Decision No. 68/PUU-XII/2014. 2) The judge's legal consideration is that the applicant has married at the Nusantara Christian Church based on Article 2 Paragraph (2) of Act Number 1 of 1974 and Article 99 KHI. 3) The children resulting from interfaith marriages is an illegitimate children based on Article 42 of the Act Number 1 of 1974 and Article 99 KHI.